High-Dose Versus Low-Dose Pitavastatin in Japanese Patients With Stable Coronary Artery Disease (REAL-CAD): A Randomized Superiority Trial. Issue 19 (8th May 2018) - Taguchi, Isao; Iimuro, Satoshi; Iwata, Hiroshi; Takashima, Hiroaki; Abe, Mitsuru; Amiya, Eisuke; Ogawa, Takanori; Ozaki, Yukio; Sakuma, Ichiro; Nakagawa, Yoshihisa; Hibi, Kiyoshi; Hiro, Takafumi; et al.
Abstract : Background: Current guidelines call for high-intensity statin therapy in patients with cardiovascular disease on the basis of several previous "more versus less statins" trials. However, no clear evidence for more versus less statins has been established in an Asian population. Methods: In this prospective, multicenter, randomized, open-label, blinded end point study, 13 054 Japanese patients with stable coronary artery disease who achieved low-density lipoprotein cholesterol (LDL-C) <120 mg/dL during a run-in period (pitavastatin 1 mg/d) were randomized in a 1-to-1 fashion to high-dose (pitavastatin 4 mg/d; n=6526) or low-dose (pitavastatin 1 mg/d; n=6528) statin therapy. The primary end point was a composite of cardiovascular death, nonfatal myocardial infarction, nonfatal ischemic stroke, or unstable angina requiring emergency hospitalization. The secondary composite end point was a composite of the primary end point and clinically indicated coronary revascularization excluding target-lesion revascularization at sites of prior percutaneous coronary intervention. Results: The mean age of the study population was 68 years, and 83% were male. The mean LDL-C level before enrollment was 93 mg/dL with 91% of patients taking statins. The baseline LDL-C level after the run-in period on pitavastatin 1 mg/d was 87.7 and 88.1 mg/dL in the high-dose and low-dose groups, respectively. During the entire course of follow-up, LDL-C in the high-dose group was lower by 14.7 mg/dL than in the low-dose group ( P <0.001). With a median follow-up of 3.9 years, high-dose as compared with low-dose pitavastatin significantly reduced the risk of the primary end point (266 patients [4.3%] and 334 patients [5.4%]; hazard ratio, 0.81; 95% confidence interval, 0.69–0.95; P =0.01) and the risk of the secondary composite end point (489 patients [7.9%] and 600 patients [9.7%]; hazard ratio, 0.83; 95% confidence interval, 0.73–0.93; P =0.002). High-dose pitavastatin also significantly reduced the risks of several other secondary end points such as all-cause death, myocardial infarction, and clinically indicated coronary revascularization. The results for the primary and the secondary composite end points were consistent across several prespecified subgroups, including the low (<95 mg/dL) baseline LDL-C subgroup. Serious adverse event rates were low in both groups. Conclusions: High-dose (4 mg/d) compared with low-dose (1 mg/d) pitavastatin therapy significantly reduced cardiovascular events in Japanese patients with stable coronary artery disease. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01042730. Abstract : Supplemental Digital Content is available in the text.